"A Cathartic Moment in a Man's Life": Homosociality and Gendered Fun on the Puttan Tour. (April 2020) - Crowhurst, Isabel; Eldridge, Adam
Rarely addressed in academic scholarship, the puttan tour is a well-known form of entertainment in Italy where young men drive around in small groups with the aim of spotting street sex workers. On some occasions, the participants will approach the sex workers to strike up a conversation. On others, they will shout out insults from their car then drive away. This article aims to advance a detailed analysis of this underexplored cultural practice drawing on a diverse body of scholarship exploring the intersection of masculinity, leisure, and homosociality. By analyzing stories of puttan tours gathered mostly online, including written accounts and YouTube videos, our aim is to explore the appeal of the puttan tour through an analysis of how homosociality, humor, and laughter operate in this example of gendered fun. To this end, we look at the multiple and often equivocal meanings of this homosocial male-bonding ritual, its emotional and affective dynamics, and the ways in which it reproduces structures of inequality while normalizing violence against sex workers.